The Influence of Rankings and Incentive Systems on Academic Publishing in South African Universities - Crain Soudien (Arizona State University, 2014)
This essay looks at the influence of ranking and incentive systems on decisions higher education institutions are making with respect to research and academic publishing. It describes and analyses how institutions within the South African higher education system have navigated their way through the contradictory forces confronting them. Characterizing these forces are, on the one hand, the country's higher education policy platform which calls for institutions to address South Africa's legacy issues of inclusion and social redress, and, on the other, the demands for institutions to maintain and grow their research profiles. The paper argues that South African institutions are struggling with this tension, as they struggle to pose, to articulate, and deliberately to respond to the question of what it means to be 'excellent'.  Drawing upon institutional documents in the public domain, this paper shows how significantly this tension animates the decisions that institutions are making about their research and publication policies and practices.